2017
DOI: 10.3390/ijms18112313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saturated Stearic Acid on MAP Kinase and ER Stress Signaling Pathways during Apoptosis Induction in Human Pancreatic β-Cells Is Inhibited by Unsaturated Oleic Acid

Abstract: It has been shown that saturated fatty acids (FAs) have a detrimental effect on pancreatic β-cells function and survival, leading to apoptosis, whereas unsaturated FAs are well tolerated and are even capable of inhibiting the pro-apoptotic effect of saturated FAs. Molecular mechanisms of apoptosis induction and regulation by FAs in β-cells remain unclear; however, mitogen-activated protein (MAP) kinase and endoplasmic reticulum (ER) stress signaling pathways may be involved. In this study, we tested how unsatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 41 publications
(63 reference statements)
2
32
0
Order By: Relevance
“…HepG2 cells incubated with or without sodium stearate. Sodium stearate represents one of the key saturated fatty acids presented in HFD and is able to significantly activate ER-stresssignaling pathways usually associated with fatty liver diseases and diabetes ( Srá mek et al, 2017). Consistent with findings in animals, overexpression of the human mutant SLC16A11 caused more triglyceride accumulation compared to cells transfected with the wild-type SLC16A11 or empty vector in HepG2 cells ( Figure 3H).…”
Section: Reconstitution Of Mutant Slc16a11 In Mouse Liver Causes Excesupporting
confidence: 83%
“…HepG2 cells incubated with or without sodium stearate. Sodium stearate represents one of the key saturated fatty acids presented in HFD and is able to significantly activate ER-stresssignaling pathways usually associated with fatty liver diseases and diabetes ( Srá mek et al, 2017). Consistent with findings in animals, overexpression of the human mutant SLC16A11 caused more triglyceride accumulation compared to cells transfected with the wild-type SLC16A11 or empty vector in HepG2 cells ( Figure 3H).…”
Section: Reconstitution Of Mutant Slc16a11 In Mouse Liver Causes Excesupporting
confidence: 83%
“…Our previous studies showed that SA, at a concentration of 1 mM, induces endoplasmic reticulum stress and apoptosis in most NES2Y cells within 24 h of application [4,35,36,37]. Therefore, all assessments were performed within 24 h after FAs application except for the assessment of cell growth and viability.…”
Section: Methodsmentioning
confidence: 99%
“…The chronic treatment of β-cells with unsaturated FAs, such as oleate, palmitoleate, and arachidonate, increased GSIS and the proliferation and survival of β-cells, and counteracted the lipotoxic effects of palmitate in rodent BRIN-BD11, INS-1E, MIN6 cell lines and human NES2Y pancreatic β-cell lines and islets, respectively [50][51][52][53]. Endocannabinoids (arachidonate derivatives) were shown to stimulate insulin secretion in INS-1E cells through cytoskeletal reorganization [54].…”
Section: Fatty Acids and β-Cell Functionmentioning
confidence: 99%